"Saviour" Politics and Malaysia's 2018 Electoral Democratic Breakthrough: Rethinking Explanatory Narratives and Implications. Issue 3 (December 2018) - Welsh, Bridget
In understanding Malaysia's surprise 14th General Election, this article argues for the need to rethink how we understand elections. We need to bring together macro socio-political forces with more micro-level evolving phenomena in the campaign, within political institutions, and in voting behaviour. Rather than buck international trends, Malaysia's sociopolitical conditions before the election – political polarisation, a rise of anger, increasing economic vulnerabilities, as well as increased nationalist and populist sentiments – echoed global trends and served as fertile ground for political change. It was however three sufficient conditions that brought about the political breakthrough: the impact of emotional campaigning through social media, the deinstitutionalisation of the dominant Malay party, United Malays National Organisation, and the failure to win over young voters – all factors that tie closely with the macro forces shaping the country. Given the factors that shaped the electoral outcome and Malaysia's "saviour politics, " it is suggested that the government turnover was more about breaking with the past than embracing democracy. As such, there will be constraints placed on expanding democracy going forward.